2020
DOI: 10.3389/fncel.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Preserves Cytochrome Oxidase Activity and Prevents Neurodegeneration and Memory Impairment in Rats With Chronic Cerebral Hypoperfusion

Abstract: Chronic cerebral hypoperfusion in neurocognitive disorders diminishes cytochrome oxidase activity leading to neurodegenerative effects and impairment of learning and memory. Methylene blue at low doses stimulates cytochrome oxidase activity and may thus counteract the adverse effects of cerebral hypoperfusion. However, the effects of methylene blue on cytochrome oxidase activity during chronic cerebral hypoperfusion have not been described before. To test this hypothesis, rats underwent bilateral carotid arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
0
8
0
3
Order By: Relevance
“…Then we used the averaged regional data from each functional neuroanatomical system to calculate standard Pearson's bivariate correlations (r-values from 1 to 0) to create correlation matrices among the systems for each of the groups. This correlative analysis using CCO activity data has been established previously as a way to estimate the modification of network functional connectivity in the rat brain (Riha et al, 2011;Vélez-Hernández et al, 2014;Auchter et al, 2020). All analyses were performed using Excel and the Statistical Package for the Social Sciences (SPSS Inc., IBM, version 221.0, Chicago, IL, United States).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Then we used the averaged regional data from each functional neuroanatomical system to calculate standard Pearson's bivariate correlations (r-values from 1 to 0) to create correlation matrices among the systems for each of the groups. This correlative analysis using CCO activity data has been established previously as a way to estimate the modification of network functional connectivity in the rat brain (Riha et al, 2011;Vélez-Hernández et al, 2014;Auchter et al, 2020). All analyses were performed using Excel and the Statistical Package for the Social Sciences (SPSS Inc., IBM, version 221.0, Chicago, IL, United States).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In order to investigate the effects of depression on functional networks, the pairwise correlations of Cys and DA were estimated across 32 brain regions of WT mice, CRS mice, and CRS mice treated with NAC [33] . To reduce the randomness of the collected data and to scale up the fiber array to larger brain networks, four mice were implanted with 32 fibers distributed across four front pieces in one hemisphere at different locations (Figures 5a and 5b).…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the effects of depression on functional networks, the pairwise correlations of Cys and DA were estimated across 32 brain regions of WT mice, CRS mice, and CRS mice treated with NAC. [33] To reduce the randomness of the collected data and to scale up the fiber array to larger brain networks, four mice were implanted with 32 fibers distributed across four front pieces in one hemisphere at different locations (Figures 5a and 5b). The selected brain regions belong to different neurobiological networks and include the following regions: medial orbital cortex (MO), lateral orbital cortex (LO), ventral orbital cortex (VO), infralimbic cortex (IL), M1, S1BF, cingulum (Cg), perirhinal cortex (PRh), primary visual cortex (V1), secondary visual cortex (V2), CPu, accumbens nucleus core (Acbc), accumbens nucleus shell (Acbs), globus pallidus (GP), submedius thalamic nucleus (Sub), laterodorsal thalamic nucleus (LD), RT, central amygdaloid nucleus (CE), BLA, DG, field CA1 of the hippocampus (CA1), field CA2 of the hippocampus (CA2), CA3, VM, ventrolateral thalamic nucleus (VL), ventral tegmental area (VTA), anterior pretectal nucleus (APT) and substantia nigra, reticular part (SNR) (Figure 5c).…”
Section: Methodsmentioning
confidence: 99%
“…These effects were accompanied by long-lasting mitochondrial respiratory function [ 33 ]. Another study showed that MB could prevent memory impairment in rats with chronic cerebral hypoperfusion [ 76 ]. With functional imaging in the human brain, it was shown that MB could modulate task-related and resting-state neural networks [ 77 ].…”
Section: Applicationsmentioning
confidence: 99%